Change in Childhood Paradigm: Project Study on “Democratisation of Pre-School Education System” (1993-2005) - Gražienė, Vitalija (Acta Paedagogica Vilnensia, 2006)
Basing on the data of research and evaluation of results, in the article "Changes in the Paradigm of the Concept of Childhood: Study of the project "Democratisation of Preschool Education System" (1993- 2005) a long-lasting international project and analysis of its impact for the development of methodological and strategic approaches in Lithuanian Early Childhood Education is presented. The process of development of the project – from treated as very alternative (but totally supported on the national level and matching the educational reform) in the first phase (1 993-2000) to full integration into context of modern strategies of educational politics (also making influence on these strategies) in the second phase (2000-2005) is analysed. Problems of effectiveness, meaningfulness, style and perspectives of international cooperation in the sphere of education (combining efforts of state structures in all – local, regional and national - levels and NGO are discussed in the context of radical political, social changes, also in the context of educational reform and challenges of globalisation processes.